DC-110 GHz Characterization of 22FDX®FDSOI Transistors for 5G Transmitter Front-End - Quang Huy Le; Dang Khoa Huynh; Defu Wang; Thomas Kämpfe; Steffen Lehmann (ESSDERC 2019-49th European Solid-State Device Research Conference (ESSDERC), 2019)
This work presents a detailed study on the high-frequency performance of 22FDX ® FDSOI for 5G front-end power amplifiers. The following report focuses on the S-parameters and large-signal figure-of-merits such as output power, gain and power-added efficiency for an insightful and correct assessment on the device capability. DC characteristics of the test transistors are firstly investigated to determine the optimum operating point. Small-signal characterization is performed up to 110 GHz using a state-of-the-art mm-Wave measurement setup. An overall MSG/MAG of 16 ± 4 dB is recorded in the frequency range 10 - 80 GHz. On the other hand, large-signal performance on non-50 Ohm impedance environment is evaluated thoroughly through vector-receiver load-pull measurement up to 24 GHz. The measured output power and efficiency indicate that the DUTs perform well in the sub-6 GHz band and even in K-band. The outstanding experimental results emphasize the applicability and suitability of the 22FDX ® FDSOI technology platform for 5G low-power transmitters.